Vegetation changes and climate shift during the latest Ladinian to the early Carnian: Palynological evidence from the Yanchang Formation, Ordos Basin, China - Li, Xiang; Zhang, Ying; Sun, Yuewu; Shi, Xiao; Zhang, Shuqin (Frontiers in Earth Science, 2023)
The Middle–Late Triassic climates have attracted the attention of paleontological and geological scientists for the Carnian pluvial event in the early Late Triassic. The event is well-documented in the pelagic and epi-continental marine deposits of the Tethys, Gondwana, and Laurasia. However, inland terrestrial deposits are less frequently depicted, with high-resolution palynological biostratigraphy constraints. In this study, we report the palynological records from the YC8-1 and YC7-3 sub-members of the Yunmeng profile in the Ordos Basin, China, where the YC7-3 was dated at 236.0–234.1 Ma. Two palynological assemblages were recognized and named the Lundbladispora watangensis–Taeniaesporites combinatus assemblage and Lundbladispora communis–Discisporites granulus assemblage for the YC8-1 and YC7-3 sub-members, respectively. Their ages were determined to be the latest Ladinian and early Carnian, respectively, for their stratigraphic correlations with the global boundary stratotype section and point (GSSP) of the base of Carnian in Europe and additional co-occurring floras with condonts in the Upper Triassic of South China. The coexistence of Cyathidites minor (Couper, 1953), Dictyophyllidites harrisii (Couper, 1958), Apiculatisporis bulliensis (Helby ex De Jersey, 1972), Aratrisporites xiangxiensis (Li and Shang, 2011), Piceaepollenites omoriciformis (Bolkh.) (Xu and Zhang, 1984), Podocarpidites ornatus (Pocock, 1962), Discisporites granulus (Zhang, 1984), and Classopollis (Pflug, 1953) is equivalent to the Carnian palynostratigraphic criterion reported in the North China palynofloristic realm. Vegetational changes, especially those occurring at the boundary between Ladinian and Carnian, account for approximately 70% of ferns and over 30% of gymnosperms lost. These were discovered and attributed to the strong seasonal arid climate, indicated by the emergence of Cheirolepidiaceae and Pinuspollenites. We thus know that the climate during the latest Ladinian and early Carnian was “hot house” with seasonal aridity. In addition, three strong monsoonal pluvial pulses were signaled by the humidity index of lowland plants. The present study will enable a better understanding the Carnian pluvial event in the Late Triassic inland basin.